PENCAIRAN DANA BOS KINERJA DAN AFIRMASI PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA MEDAN - Egla Margaretta Meliala; Muhammad Heru Akhmadi (Journal Publicuho, 2021)
Education is two of the four national aims specifically in order to advance general prosperity and to develop the nation’s intellectual life. In the present time, the accessibility of education in remote areas, the building of characters, as well as the advances of technology has become challenges of education system due to lack of capabilities of skilled resources. In coping with those matters, the government allocates the Affirmation and Performance School Operational Assistance Funds in conjunction with the school's digitalization program to deal with 4.0 industrial revolution. This research is aimed at finding out the process of distribution of the Affirmation and Performance School Operational Assistance Funds in State Treasury Services Office I of Medan and the management implementation of the Performance School Operational Assistance Funds in St. Ignasius Medan High School. This research uses qualitative methods by using the ATLAS.ti application tools to create network knowledge. The research findings show that the distribution and management of the Affirmation and Performance School Operational Assistance Funds has been progressing well despite having some issues. Some of the issues are the invalid school account data and the changing of School Operational Assistance Funds regulations. Those issues resulted in the high return of accounts and the difficulty in formulating financial reporting of the Performance School Operational Assistance Funds.